Shifting power dynamics? The role of civil society organizations in the policymaking for Mozambique’s extractive sector - Sanches, E.; Julio, N. (Forum for Development Studies, 2021)
In 2012 the Mozambican government announced the revision of the mining and petroleum laws in consultation with civil society organizations (CSOs). This followed the discovery of world class gas reserves in the Rovuma Basin, and growing demands for transparency, fair sharing of revenues and protection of national interests, from all quadrants. Given this, what was the role played by CSOs? Did they influence the process at all, or did the consultation serve as a tool to strengthen the regime’s interests and legitimacy? Building on Gramsci and African scholarship that conceptualizes the state and civil society as relational social forces that co-influence each other through shifting power balances, the study reveals that CSOs influenced the development of the mining and petroleum laws by performing four essential roles: expertise, agenda-setting, representative and monitoring. The government accommodated some of CSOs demands, even though the consultation process was not fully open. The findings build on a mix of interviews with members of CSOs and other qualitative sources (laws, news and reports) and underline the need to analyse state and civil society beyond dichotomous and homogenizing categories. They also contribute to a flourishing literature on the role of civil society in competitive authoritarian regimes.